Improved metal allergen reactivity of artificial skin models by integration of Toll‐like receptor 4‐positive cells. (4th July 2019) - Frings, Verena G.; Müller, Damaris; Storz, Gabriel; Rossi, Angela; Sennefelder, Helga; Adam, Christian; Goebeler, Matthias; Groeber‐Becker, Florian K.; Schmidt, Marc
Abstract: Background: Reconstructed human epidermis (RhE) is widely used to replace animal models in order to assess the proinflammatory and allergenic effects of chemicals. Unfortunately, RhE lacks proinflammatory responsiveness for metal haptens, which are the most prevalent human contact allergens, raising concerns about its reliability for predicting skin allergens. Objectives: To investigate whether this limitation of RhE might be attributable to a lack of functional expression of Toll‐like receptor 4 (TLR4), which governs proinflammatory sensitivity to nickel and cobalt. Materials and Methods: RhE, dendritic cell (DC)‐containing RhE and full‐thickness skin equivalent (FTSE) were compared regarding their proinflammatory responsiveness to metal allergens. Results: The incorporation of dermal fibroblasts was sufficient to confer metal sensitivity to RhE. Unlike keratinocytes, normal human fibroblasts expressed high levels of TLR4 mRNA and induced interleukin‐8 expression upon stimulation with nickel or cobalt. Consistently, dermal isolates from FTSE expressed considerable amounts of TLR4 mRNA, whereas RhE or epidermis isolated from FTSE, normal human epidermis or inflamed human epidermis failed to express TLR4. Similarly, co‐culture with TLR4‐positive DCs bestowed RhE with proinflammatory responsiveness to metals. Conclusion: Our data suggest that FTSE or DC/RhE co‐culture models can circumvent the shortcomings of RhE assays, and combine the benefits of complex and monoculture‐based test systems in a single assay.